Comparison of the perioperative outcomes of robotic vs. open distal pancreatectomy: a meta-analysis of propensity-score-matched studies - Wang, Junjie; Liu, Yuanjun; Wu, Yakun (Frontiers in Surgery, 2025)
ObjectiveRobotic distal pancreatectomy (RDP) is considered to offer certain advantages over traditional open distal pancreatectomy (ODP); however, high-quality evidence remains limited. This meta-analysis aimed to compare perioperative outcomes between RDP and ODP using data from propensity-score–matched studies.MethodsA systematic literature search was performed using the PubMed, Cochrane Library, Embase, and Web of Science databases for studies comparing RDP and ODP. Odds ratios (ORs) and mean differences (MDs) with 95% confidence intervals (CIs) were calculated.ResultsSeven studies with 1,526 patients were included (RDP group: 722 patients; ODP group: 804 patients). Compared with ODP, RDP was associated with a shorter hospital stay (MD −3.11 days; 95% CI, −4.45, −1.77), reduced blood loss (MD −163.38 mL; 95% CI, −212.08, −114.68), higher spleen preservation rates (OR 2.36, 95% CI, 1.06, 5.24) and lower surgical site infection (SSI) rates (OR 0.47, 95% CI 0.29, 0.76). No significant differences were found in 90-day mortality, overall morbidity, major complications, operative time, reoperation rates, postoperative pancreatic fistula, number of harvested lymph nodes, and R0 resection rates.ConclusionsThis meta-analysis suggests that RDP may have potential advantages over ODP, including reduced blood loss, shorter hospitalization, higher spleen preservation, and lower SSI rates. These potential benefits warrant confirmation in future randomized controlled trials.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251031280, PROSPERO CRD420251031280.